Mastering Alliance Strategy A Comprehensive Guide to Design, Management, and Organization - Benjamin Gomes-Casseres , James D. Bamford (Jossey-Bass)
Alliances have come of age. In the last ten years, they have gone from being a peripheral tool of management, used mostly to enter restricted overseas markets, to a centerpiece of corporate strategy and competitive advantage. Today, many companies have portfolios of twenty or more alliances—and some have more than a hundred. Because of this, it is now common to see alliances account for 20–50 percent of corporate value—whether measured in terms of revenues, assets, income, or market capitalization. Alliances are fueling the success of a wide range of firms, including British Petroleum, Eli Lilly, General Electric, Corning Glass, Federal Express, IBM, Starbucks, Cisco Systems, Millennium Pharmaceuticals, and Siebel Systems.